SnRK2 Protein Kinases—Key Regulators of Plant Response to Abiotic Stresses - Kulik, Anna (Mary Ann Liebert, Inc., 2011)
The SnRK2 family members are plant-specific serine/threonine kinases involved in plant response to abiotic stresses and abscisic acid (ABA)-dependent plant development. SnRK2s have been classed into three groups; group 1 comprises kinases not activated by ABA, group 2 comprises kinases not activated or activated very weakly by ABA, and group 3 comprises kinases strongly activated by ABA. So far, the ABA-dependent kinases belonging to group 3 have been studied most thoroughly. They are considered major regulators of plant response to ABA. The regulation of the plant response to ABA via SnRK2s pathways occurs by direct phosphorylation of various downstream targets, for example, SLAC1, KAT1, AtRbohF, and transcription factors required for the expression of numerous stress response genes. Members of group 2 share some cellular functions with group 3 kinases; however, their contribution to ABA-related responses is not clear. There are strong indications that they are positive regulators of plant responses to water deficit. Most probably they complement the ABA-dependent kinases in plant defense against environmental stress. So far, data concerning the physiological role of ABA-independent SnRK2s are very limited; it is to be expected they will be studied extensively in the nearest future.